Investigating EFL Students’ Errors in Using Time and Place Prepositions - Muhassin, Mohammad; Octavia, Sonia (KAMBOTI: Jurnal Sosial dan Humaniora, 2021)
The study tries to investigate the types of grammatical error of time and place prepositions, and to notice the error percent of the tenth-grade students of State Islamic Senior High School (MAN) 1 Bandar Lampung, Lampung Indonesia. The research design is descriptive qualitative using an error analysis (EA) framework. There were 31 students as the research participant chosen by using purposive sampling procedure. The data were obtained from documentation of learners’ essay writing and analyzed using Surface Strategy Taxonomy to categorize them. In addition, the writer calculated the proportion of errors found. The findings indicate that students made 27 items (25%) of omission, 25 items (24 %) of addition, 30 items (28%) of misformation, 24 items (23%) of misordering. Errors of misformation were found the most, whereas the errors of misordering were found the least. The errors were often caused by L1 interference, carelessness, and literal translation. Certain pedagogical implications along with the research suggestions were also discussed.